A Novel Hybrid Backstepping and Fuzzy Control for Three Phase Induction Motor Drivers - Pham, Ngoc Thuy; Nguyen, Phu Diep (Association for Scientific Computing Electronics and Engineering (ASCEE), 2025)
High-performance control using three-phase Induction Motors (IM) is increasingly required in industrial applications. However, due to the nonlinear structure and the continuous impact of issues such as load disturbances and motor parameter variations, traditional control techniques cannot achieve the desired high-performance drive system. In this paper, a new hybrid control scheme combining Backstepping (BS) with fuzzy logic (FL) control for the outer speed control loop to enhancing Field Oriented Control (FOC) vector control performance of the SPIM drives, is proposed. Different from the BS control strategies that have been proposed in the control of IM drive systems before, this paper proposes to use FL control theory to continuously update the coefficients appearing in the virtual control vectors extracted from the traditional BS control technique according to the input error of the system. This contributes to improving the performance of the drive system, enhancing the stability and adaptability of the drive system. Lyapunov stability theory is used to design the drive system to ensure the stability of the overall system. The proposed speed control strategy is validated through Matlab-Simulink. The simulation results show that: first, the proposed control strategy provides fast speed response, and the convergence capability of the drive system remains in an optimal state during transient modes without causing overshoot. Second, the drive system operates stably over the long term under load disturbances.